THE ESTIMATION OF INDICATORS OF CENTRAL HAEMODYNAMICS IN INTERRELATION WITH TOLERANCE TO PHYSICAL ACTIVITY AT PREGNANT WOMEN WITH MYOCARDITIS - F. A. Zakirova; I. R. Bekbulatova; R. B. Yusupbaev (Евразийский Кардиологический Журнал, 2015)
Within the limits of research indicators of central hemodynamics in interrelation with tolerance to physical activity at pregnant women with myocarditis were estimated. 109 pregnant women from 19-35 years in 2 trimester gestosis are surveyed. Spent an electrocardiogram, EhoKG with definition a myocardial working index, test with physical activity. Results have shown that frequency of heartbeat, average pulmonary pressure, the sizes left ventricle authentically higher in group of pregnant women with myocarditis that is accompanied by decrease contractile abilities of a myocardium and an index myocarditis a reserve. The length of the passed distance the walking 6 minute test is more in group of healthy women. Direct correlation dependence between the passed distance and factor myocarditis a reserve in group of pregnant women with myocarditis is defined.